Photo‐Induced Click Chemistry for DNA Surface Structuring by Direct Laser Writing. Issue 21 (27th March 2017) - Kerbs, Antonina; Mueller, Patrick; Kaupp, Michael; Ahmed, Ishtiaq; Quick, Alexander S.; Abt, Doris; Wegener, Martin; Niemeyer, Christof M.; Barner‐Kowollik, Christopher; Fruk, Ljiljana
Abstract: Oligonucleotides containing photo‐caged dienes were prepared and shown to react quantitatively in a light‐induced Diels–Alder cycloaddition with functional maleimides in aqueous solution within minutes. Due to its high yield and fast rate, the reaction was exploited for DNA surface patterning with sub‐micrometer resolution employing direct laser writing (DLW). Functional DNA arrays were written by direct laser writing (DLW) in variable patterns, which were further encoded with fluorophores and proteins through DNA directed immobilization. This mild and efficient light‐driven platform technology holds promise for the fabrication of complex bioarrays with sub‐micron resolution. Abstract : A laser pen for DNA writing : Photoactive oligonucleotides were patterned onto a maleimide‐coated glass surface using direct laser writing (DLW) and light‐induced Diels–Alder cycloaddition. The patterns with sub‐micrometer resolution can further be used for the immobilization of various molecular species such as fluorophores and proteins.